Effect of additon amount of carbon black on curing characteristics, physical and mechanical properties, and dynamic mechanical properties of tetrafluoroethylene-propylene rubber - GONG Zi-qing, LI Bo, HE Lian-cheng, HUANG Xi-dai, ZHAO Hong-guo, WU Yu, HU Hai-hua, ZHOU Lei (Hecheng xiangjiao gongye)
The effect of carbon black addition amount on curing characteristics of tetrafluoroethylene-propylene rubber compounds and physical and mechanical properties, dynamic mechanical properties and high- and low-temperature properties of the vulcanizates were studied. The results showed that with the increase in the addition amount of carbon black, Mooney viscosity and minimum torque of compounds increased, scorch time had no obvious change, the vulcanization rate first decreased and then tended to be stable, and the crosslinking density of vulcanizates first increased and then decreased. Both tensile strength and elongation at break of the vulcanizate by the one-stage vulcanization process showed a decreasing trend, while modulus at 100% and Shore A hardness showed an increasing trend. Shore A hardness, modulus at 100% and tensile strength of the vulcanizate by the two-stage vulca-nization process improved significantly compared with those of the vulcanizate by the one-stage vulcanization process. With the increase in the addition amount of carbon black, the glass transition region of the vulcanizates became narrow significantly, the glass transition temperature moved to the low temperature direction, and meanwhile the loss factor at 200 ℃ increased, both the storage modulus and loss modulus first increased and then remained essentially constant.